2014
DOI: 10.1158/1078-0432.ccr-13-2070
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Dose-Escalation Study of Onartuzumab as a Single Agent and in Combination with Bevacizumab in Patients with Advanced Solid Malignancies

Abstract: Purpose: This first-in-human study evaluated the safety, immunogenicity, pharmacokinetics, and antitumor activity of onartuzumab, a monovalent antibody against the receptor tyrosine kinase MET.Experimental Design: This 3þ3 dose-escalation study comprised three stages: (i) phase Ia dose escalation of onartuzumab at doses of 1, 4, 10, 20, and 30 mg/kg intravenously every 3 weeks; (ii) phase Ia cohort expansion at the recommended phase II dose (RP2D) of 15 mg/kg; and (iii) phase Ib dose escalation of onartuzumab … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 25 publications
1
43
0
1
Order By: Relevance
“…Although sample size was limited, no relationship was observed between dose and emibetuzumabrelated AEs. Peripheral edema has been suggested as a potential on-target class effect for therapies targeting the MET/HGF pathway (17). Ryan and colleagues (18) noted peripheral edema by treatment with rilotumumab (a fully human mAb against HGF), and Salgia and colleagues reported peripheral edema following treatment with onartuzumab (a monovalent MET Ab) at doses !10 mg/kg (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sample size was limited, no relationship was observed between dose and emibetuzumabrelated AEs. Peripheral edema has been suggested as a potential on-target class effect for therapies targeting the MET/HGF pathway (17). Ryan and colleagues (18) noted peripheral edema by treatment with rilotumumab (a fully human mAb against HGF), and Salgia and colleagues reported peripheral edema following treatment with onartuzumab (a monovalent MET Ab) at doses !10 mg/kg (17).…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral edema has been suggested as a potential on-target class effect for therapies targeting the MET/HGF pathway (17). Ryan and colleagues (18) noted peripheral edema by treatment with rilotumumab (a fully human mAb against HGF), and Salgia and colleagues reported peripheral edema following treatment with onartuzumab (a monovalent MET Ab) at doses !10 mg/kg (17). In the current study, non-emibetuzumab-related peripheral edema was reported for monotherapy in 2 patients at the lowest dose level, and 1 patient each at the 700-mg and 1,400-mg dose levels.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of clinical activity of treatment with c-MET inhibitors for the 7 MET-amplified patients reported here was disappointing. Results from prior trials detected early activity of these agents in patients selected by c-MET protein overexpression and MET amplification in GECs (7,44), MET germline mutations in papillary renal cell cancer (24), and chromosome polyploidy in gastric cancer (45). However, it is to be noted, for patients with NSCLC, both onartuzumab and tivantinib in combination with EGFR did not meet their endpoints in an unselected population.…”
Section: Discussionmentioning
confidence: 99%
“…Also, recurrent amplification of genes associated with the receptor tyrosine kinase pathway, such as EGFR, ERBB2, ERBB3, JAK2, FGFR2, and MET, and the angiogenesis pathway, such as VEGFA, have been reported in GC [4,5]. With the exception of a subset of patients with ERBB2 amplification who experienced benefits from trastuzumab [6], targeted agents for aberrant gene amplification have not yet been successful in therapeutic applications [7][8][9].…”
Section: Introductionmentioning
confidence: 99%